DESKRIPTIF KUALITATIF ALASAN MAHASISWA AKUNTANSI FAKULTAS EKONOMI UNPATTI MEMILIH KONSENTRASI AKUNTANSI SEKTOR PUBLIK - Zalni, Zalni; Fauzan Z, M. Rifkhi; Putuhena, Hempry (JURNAL LENTERA AKUNTANSI, 2023)
This study aims to find out the reasons students majoring in accounting at the Faculty of Economics, Pattimura University decided to choose a concentration in public sector accounting, to be precise, students in their sixth semester of the 2022/2023 academic year. This research is a type of qualitative research using an interpretive paradigm. Retrieval of data using interviews packaged in the form of Fucus Group Discussion. The results showed that the reasons for students choosing the ASP (Public Sector Accounting) concentration were due to the preparation of their final project, preferred career goals, factors of interest in Public Sector Accounting, perceptions of wider availability of employment opportunities, perceptions of ASP courses tend to be easier, as well as factors teaching lecturer. Another finding is that almost all respondents are interested in a career as a government employee, although not all stated that the reason for choosing the ASP concentration was because of this.Keywords: Concentration, Accounting, Public, Qualitative, Interpretive